Measurement of plasma atrial natriuretic peptide as an indicator of prognosis in dogs with cardiac disease - Greco, Deborah S. (Can Vet J, 2003)
Twenty-three dogs with heart failure were evaluated in a 12-month study by measuring baseline plasma atrial natriuretic peptide (ANP) concentrations. Ten dogs were classified as having mild to moderate cardiac disease (group 1) and 13 dogs were classified as having severe cardiac disease (group 2). The mean plasma ANP concentration for the group 1 dogs was 64 ± 45 pg/mL and for the group 2 dogs, 328 ± 122 pg/mL. The median survival time (1095 d) for group 1 dogs was significantly greater (P < 0.05) than for group 2 dogs (58 d). A significantly (P , 0.05) greater median survival was noted for dogs with plasma ANP , 95 pg/mL (1095 d) compared with those with ANP . 95 pg/mL (58 d). Plasma ANP concentrations are a potential noninvasive predictor of survival in dogs with heart failure.